Managing America's Small Communities: People, Politics, and Performance - Folz, David H.; French, Edward P. (Rowman & Littlefield Publishers, 2005)
Managing America's Small Communities charts several key aspects of the largely unexamined world of small city management. This book describes the democraphic trends, structural features, executive behavior and service quality among small communities. Are small cities growing, declining or have they remained untouched by the force of change? To what extent have the structural changes and reforms that have swept through larger cities touched small communities? What are the characteristics and behaviors of small city chief executives and how involved are different executives in the dimensions of the governmental process? How do chief executives in small cities make decisions about local services and programs? Are there differences in the extent to which appointed managers and elected mayors are responsive to community interests? The book also examines the frequency with which small communities provide various services, the quality of services provided and how small city officials can diagnose problems with service quality and performance. The book's theme is the value added to small communities that evidence professionalism in city administration. The benefits that accrue to having a professional city manager are most apparent in the extent to which city managers are engaged in decisions related to each of the dimensions of the governmental process, the level of service quality provided, and the prospects for measuring service performance.